The Influence of System Quality, User Satisfaction and Effort Expectancy on User Adoption of Information Systems of Mobile Banking Users - Setiadi, Bekti; Apramilda, Riesna; Syahviyar, Mirza; Mustafa, Fahrina; Violin, Vivid; Latief, Yanuar (Journal of Information System, Technology and Engineering, 2025)
This research proposes to evaluate the effect of system quality, user satisfaction, and effort expectancy on information systems user adoption among Indonesian mobile banking consumers. The​‍​‌‍​‍‌ research method employed was quantitative, involving a survey of 200 respondents who are mobile banking users and belong to different banking institutions. The sampling strategy used was purposive sampling based on the criteria of active users who have been using digital banking services for at least six months. Data analysis was done using multiple linear regression at a 0.05 significance level. The findings revealed that all the independent variables had a positive and significant influence on the dependent variable. System quality increases trust and effectiveness of use, user satisfaction leads to user loyalty, and effort expectancy makes the adoption of digital technology easier. Theoretically, the study extends the conversation of the DeLone and McLean Information Systems Success Model and UTAUT in digital banking. Practically, it acts as a guide to banks on how to improve their system quality, user experience, and technology acceptance level during the digital transformation ​‍​‌‍​‍‌era.